2004
DOI: 10.1021/nl0497981
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Cage-like Structures Derived from Polyisoprene-Containing Shell Cross-linked Nanoparticle Templates

Abstract: Hollowed materials of nanoscopic dimensions offer exciting possibilities in a number of fields such as therapeutics and imaging. The production of nanoscopic cage-like materials is described, based upon the excavation of shell cross-linked nanoparticle (SCK) templates. This report focuses upon extensive characterization of the ozonolysis reaction conditions used to degrade the core material, which demonstrates that thirty minutes of ozone treatment is optimal. The resulting nanocage is also shown to undergo pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 47 publications
0
62
0
Order By: Relevance
“…Hence, they can be also utilized for the controlled formation of hollow nanostructures. [108][109][110] The general fabrication procedure is as follows: i) synthesis of block copolymer composed of a crosslinkable block and a degradable block; ii) micellization; iii) crosslinking of the shell block; iv) removal of the core block by chemical degradation. Wooley's group has studied the fabrication of hollow nanospheres by ozonolysis of shell-crosslinked micelles consisting of a series of block copolymers.…”
Section: Polymer Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they can be also utilized for the controlled formation of hollow nanostructures. [108][109][110] The general fabrication procedure is as follows: i) synthesis of block copolymer composed of a crosslinkable block and a degradable block; ii) micellization; iii) crosslinking of the shell block; iv) removal of the core block by chemical degradation. Wooley's group has studied the fabrication of hollow nanospheres by ozonolysis of shell-crosslinked micelles consisting of a series of block copolymers.…”
Section: Polymer Nanostructuresmentioning
confidence: 99%
“…Poly(isoprene-b-acrylic acid) (PI-b-PAA) diblock copolymers formed micelles with a PI core and a PAA shell in an aqueous solution. 108 The PAA shell was crosslinked with a diamino crosslinker, 2,2'-(ethylenedioxy)bis(ethylamine), and the PI core could be removed by ozonolytic degradation. Similarly, poly (ε-caprolactone-b-acrylic acid) (PCL-b-PAA) diblock copolymers formed micelles with a PCL core and a PAA shell in an aqueous solution.…”
Section: Polymer Nanostructuresmentioning
confidence: 99%
“…Core-polymerization was employed to stabilize micelles of heterotelechelic amphiphilic block copolymers containing polymerizable groups at the ends of hydrophobic blocks [234]. Wooley et al have developed cage-like nanostructures on the base of polymeric micelles with hydrophobic core and cross-linked anionic shell [155,235,236]. In addition micelles with cross-linked ionic cores were prepared by self-assembly of ionic blocks of double hydrophilic block copolymers with a condensing agent, followed by chemical cross-linking of ionic blocks [153].…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…There are many reports on pH-sensitive polymeric nanospheres and hollow spheres in the literatures [6,7,[18][19][20][21][22][23][24][25][26]. Wooley et al [6,18] reported a sophisticated procedure containing successive steps: micellization of a block copolymer in the selective solvent forming a degradable core and cross-linkable shell, crosslinking the shell and chemical degradation of the core.…”
Section: Ph-sensitive Polymeric Nanospheres and Hollow Spheresmentioning
confidence: 99%
“…Wooley et al [6,18] reported a sophisticated procedure containing successive steps: micellization of a block copolymer in the selective solvent forming a degradable core and cross-linkable shell, crosslinking the shell and chemical degradation of the core. Thus, for example, pH-sensitive hollow spheres (or nanocages) of crosslinked poly(acrylic acid) (PAA) were obtained thereby.…”
Section: Ph-sensitive Polymeric Nanospheres and Hollow Spheresmentioning
confidence: 99%